If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 6 = 7x + -21 Reorder the terms: 6 + 5x = 7x + -21 Reorder the terms: 6 + 5x = -21 + 7x Solving 6 + 5x = -21 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 6 + 5x + -7x = -21 + 7x + -7x Combine like terms: 5x + -7x = -2x 6 + -2x = -21 + 7x + -7x Combine like terms: 7x + -7x = 0 6 + -2x = -21 + 0 6 + -2x = -21 Add '-6' to each side of the equation. 6 + -6 + -2x = -21 + -6 Combine like terms: 6 + -6 = 0 0 + -2x = -21 + -6 -2x = -21 + -6 Combine like terms: -21 + -6 = -27 -2x = -27 Divide each side by '-2'. x = 13.5 Simplifying x = 13.5
| 4x^3+6x^2+20x= | | 5-3(w+4)=7 | | c-1/4(c)=49.95 | | -x^2-x+7=0 | | -x+-x+x=90 | | -17=4-3x | | 12x^2+11xy-15y^2=0 | | 5b^2+17b+6=0 | | -5(46+4)+(21b-8)=0 | | 425=.85x | | -18=8-2x | | 3(t+36)=150 | | 14=-6+4x | | 8a^2+37a-15=0 | | 3b^2-3b+7b=0 | | 47=.08x | | (2m^2)(4m^4)(8n)=0 | | 3x(t+36)=150 | | ln(x)-ln(x+1)-ln(x)=0 | | p-0.15(p)=11.01 | | (2x^2)(4m^4)(8n)=0 | | (2x^2)(4m^4)(8n)=0 | | 3d^2+11d-20=0 | | 5(x-4)+x-4=2x+2(8) | | -5(46+4)+(216-8)=0 | | 59=68x | | c/6+25.75=90.30 | | 18=10+2x | | 14x=6x+56 | | 1.2(c)+2.6(c)=4.56 | | 11x^2-31x-6=0 | | Z^2+3z-40=0 |